The role of Affirmative Action in Establishing Egalitarian Society (Philosophy and Progress, 2025)
This paper aims to show how an affirmative action program—one of the most notable initiatives introduced in the last few decades—contributes to establishing a greater egalitarian society. The philosophical debate over equality, diversity, and discrimination is well known. Nowadays, equality often receives more attention than diversity and discrimination. One straightforward reason for focusing on equality is its connection to the concepts of rights, liberty, property, justice, and so on. Although the concepts related to equality can be defined relatively easily, equality itself remains elusive. This does not imply that the term equality lacks a plausible definition; rather, it can be characterized in various ways, which inevitably brings diversity into the discussion. Although diversity is sometimes viewed as negatively, it plays a pivotal role in keeping human society balanced. Moreover, without diversity, the fundamental purpose of society would be impaired. Thus, it appears that a fully egalitarian society—one in which everyone is alike in every respect—is impossible. If so, in what sense do we envision an egalitarian society and how can we establish that society? In essence, the ideal egalitarian society we envision is one where everyone is granted equal opportunities— and where even those who may struggle to fully utilize those opportunities can still benefit through measures such as affirmative action.Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 209-226